Bis-pseudorotaxane Formation of Perylene Bisimide-Linked [60]Fullerene Dumbbell-Like Molecules with [10]Cycloparaphenylene - Solymosi, Iris; Sabin, Juan; Maid, Harald; Friedrich, Lea; Nuin, Edurne; Perez-Ojeda Rodriguez, Maria Eugenia; Hirsch, Andreas (Organic Materials, 2022)
Two [60]fullerene dumbbell-like molecules with a single or double perylene-3,4,9,10-tetracarboxylic acid bisimide (PBI) linker were synthesized to study the structural and photophysical properties in addition to the complex formation with [10]cycloparaphenylene ([10]CPP). Due to their special optical properties, it is possible to describe the complexation using conventional spectroscopic methods such as NMR and fluorescence. However, isothermal titration calorimetry (ITC) was used to complete the analysis of the bis-pseudorotaxane formation by investigating the binding stoichiometries as well as the thermodynamic and kinetic parameters. It was observed that the PBI bridges do not inhibit the complexation with [10]CPP, giving rise to the formation of 1 : 1 and 1 : 2 complexes in o-dichlorobenzene with affinities of around 105 · M−1, similar to the [10]CPP⊃C60 reference system. A novel global analysis by combination of data sets from different techniques allowed us to follow the species distribution very precisely. ITC has proven to be a very powerful method for studying the complexation between fullerene derivatives and strained carbon nanohoops, which provides not only binding affinities and stoichiometries, but also all thermodynamic and kinetic parameters of the bis-pseudorotaxane formation. These results are of significant interest for the investigation of fullerene complexes in supramolecular chemistry and for their future applications in semiconductors and optoelectronic
Keywords: supramolecular chemistry - host–guest systems - fullerenes - perylene bisimide - macrocycles - cyclophanes - carbon nanobelts